Report on the Peel River and tributaries, Yukon and Mackenzie [electronic resource] - Camsell, Charles, 1876-1958.; Geological Survey of Canada. (Ottawa : S.E. Dawson, 1906)
Cover title. At head of title: Geological Survey of Canada . "Selected list of reports (Since 1885) of special economic interest published by the Geological Survey of Canada": 3 p. (at end) "No. 951." Electronic reproduction. Mode of access: Internet. 44